LEVEL OF PHYSICAL ACTIVITY IN BRAZILIAN UNIVERSITY STUDENTS: A SYSTEMATIC REVIEW (Fiep Bulletin - online, 2017)
Introduction: The level of physical activity (LFA) is related to the reduction of various diseases. For this reason, effortshave been made to promote it in the population through minimum recommendations capable of provoking health benefits.Physical activity is defined as any bodily movement, produced by skeletal muscles, which results in energy expenditure, higherthan rest levels. In addition, it is an important health factor, it is a source of leisure, balance, and motivation for life, as well as afundamental factor for socialization, and thus, Physical Activity is considered an important factor in promoting health and Qualityof life of the population. Objective: To determine, through a systematic review, the level of physical activity in Brazilian universitystudents. Methods: The research was carried out in the SciELO, Google Academic, Virtual Health Library databases, using twosets of intersection of terms of bibliographic search for the accomplishment of the research such as: Physical Activity Level,University Students (academics, University students, students of higher education, as well as their translations into English andSpanish). 42 items found. Among the articles found, 31 articles were selected for the review, of which 11 met the inclusion criteriaand 20 the exclusion criteria. Results: It was verified that there was difference when comparing the level of Physical Activity of themasculine sex with the feminine one, being observed that the men are more active than the women, verifying that the masculinegender had superior average of NAF contributing of positive form for him be considered more active daily. Conclusion: Accordingto the results, we can highlight that the majority of Brazilian university students are active. Although most students are active, apercentage is considerably sedentary.